Mapania multiflora, a distinctive new species of Cyperaceae (Mapanioideae) from Borneo - Shabdin, Z.; Culham, Alastair; Simpson, David A.; Meekiong, K. (Springer London, 2013)
Mapania multiflora is described and illustrated. It is vegetatively similar to taxa with broad leaves and pseudopetioles, such as M. cuspidata. However, it is reproductively similar to sect. Thoractostachyum with a paniculate inflorescence and furrowed fruit. The DNA is similar to M. bancana in sect. Thoractostachyum, in the three sampled cpDNA regions: atpH-F, trnL-F and psbA-trnH. However, it is identical to none of these due to its unique combination of vegetative, reproductive and molecular characteristics